(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
The aim of this research is to provide a meta-theoretical framework for theconceptualisation of the role of the corporate communication strategist. The latter haspreviously been conceptualised by the author as a role at the top management ormacro level of the organisation. It entails gathering, interpreting and disseminatingstrategic intelligence on stakeholders and issues amongst decision-makers (obtainedby means of environmental scanning) - to be used as input in the organisation'sstrategy formulation processes.The problem addressed in this research is the changing role of business in society andhow the corporate communication function could assist the organisation in achievinga balance between commercial imperatives and socially responsible behaviour. Sevenapproaches to the role of business in society are identified and discussed. It is suggestedthat the meta-theoretical approach to the conceptualisation of the role of the strategistis a synthesis of six of these approaches, namely the social responsibility/ethical approach,corporate social responsiveness approach, the corporate social performance approach, thestakeholder approach, the issues approach and the corporate community approach.